Edukasi Program Exercise Mandiri dalam Mencegah LBP pada Karyawan USC Malang - Nyalawati Ambar Pratiwi; Safun Rohmanto (Health Care : Journal of Community Service, 2026)
Background: Low Back Pain (LBP) is a musculoskeletal disorder frequently encountered in the working population, particularly those involving static activities such as prolonged sitting with poor posture. Administrative and operational staff at Unggul Sport Center are at high risk of experiencing this complaint due to long hours of desk work. Objective: This study aims to develop the concept and effectiveness of a print/digital media-based independent exercise education program as a preventive measure for LBP in Unggul Sport Center employees. Methods: This article uses a scientific literature review approach and a descriptive case study to design LBP prevention education media that includes an introduction to the signs, symptoms, and causes, as well as a regular stretching program related to every 30 minutes with an 8x1 count scheme, as well as morning exercises with a 2x8 count scheme. Results: Structured postural education and stretching interventions have been shown to significantly reduce low back muscle tension, improve trunk alignment, and prevent the accumulation of soft tissue fatigue due to prolonged sitting. Conclusion: Consistent implementation of an independent exercise education program in the Unggul Sport Center workplace can be an effective preventive strategy to reduce the incidence of low back pain and optimize employee productivity.